Restructuring of Rural Governance in a Rapidly Growing Resource Town: The Case of Kitimat, BC, Canada - Laura Ryser; Greg Halseth; Sean Markey (EchoGéo)
A new era of industrial development is unfolding in resource-dependent regions. In Canada, the local government context in these regions, however, is very different now than when industrial resource development expanded in the 1950s and 1960s. Drawing upon our case study in Kitimat, British Columbia, we highlight transformations associated with neoliberal policies that have affected rural governance. Neoliberal public policy shifts include wider changes where the state has become less involved in program and infrastructure investments in resource-dependent communities. Even as this political economy continues to evolve, past neoliberal policy responses continue to restrict local supports, while also failing to provide a comprehensive strategy to guide rapidly changing communities. In Kitimat, this has prompted a variety of responses emblematic of a shift from government to governance. The town has become more entrepreneurial and innovative to strengthen and diversify their economy. The abandonment of top-down policy levers has prompted community groups to pursue a greater voice in decision-making by opening up public participation in new planning and development processes. While new rural governance arrangements have provided positive and proactive contributions to emerging pressures, concerns persist about the long-term viability of these structures without a renewed vision, and accompanying policy, from senior governments to support rural communities and regions.